2012
DOI: 10.1111/j.1447-0594.2011.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival period after tube feeding in bedridden older patients

Abstract: Survival periods after tube feeding for less than 1 year were primarily determined by being bedridden for more than half a year without tube feeding and once pneumonia occurred; patients who were tube fed did not survive for more than half a year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In vitro studies suggested an alternative mechanism of diminished neutrophil bactericidal activity by omeprazole . Elderly bedridden patients receiving tube feeding were shown to have high mortality due to pneumonia, and the present study shows that PPI can increase the risk of and mortality due to pneumonia in this high‐risk patient population.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In vitro studies suggested an alternative mechanism of diminished neutrophil bactericidal activity by omeprazole . Elderly bedridden patients receiving tube feeding were shown to have high mortality due to pneumonia, and the present study shows that PPI can increase the risk of and mortality due to pneumonia in this high‐risk patient population.…”
Section: Discussionsupporting
confidence: 53%
“…Nasogastric tube (NGT) and gastrostomy tube placement are useful to maintain enteral access for nutrition, hydration and medication for patients with dysphagia due to stroke, brain injury, neurodegenerative diseases and obstruction due to cancer. However, previous studies reported a poor prognosis in elderly patients with tube feeding, mainly due to complications of aspiration pneumonia . Furthermore, elderly tube‐fed patients might have several risk factors for gastrointestinal bleeding, such as aging, history of esophagitis and peptic ulcer, antiplatelet and anticoagulant therapy, and gastrostomy tube placement, and are often treated with acid‐suppressive medications.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly patients who eat little, cannot give meaningful spoken responses, and are bedridden with three episodes of pneumonia have a mean survival of 6 months, even when tube-fed during the end stage of life (Kosaka et al 2012). In aged-care facilities, when the initiation of tube feeding was being discussed, if the question was phrased as, "Ninety percent of people say they would not want this procedure; do you want to go ahead with it?"…”
Section: How To Prevent the Need For Nursing Carementioning
confidence: 99%
“…In particular, a large number of residents of institutions are bed-confined. A survey of the causes of death of bedridden patients found that 68.1% died of pneumonia1 ) . As a consequence, pneumonia overtook cerebrovascular disease in 2011 to become the third most common cause of death in Japan.…”
Section: Introductionmentioning
confidence: 99%